PENERAPAN PENDIDIKAN CERDAS BERKARAKTER DI MERAUKE (PERSPEKTIF KOMUNIKASI) - Ririt Yuniar; Rafika Puspitasari (IAIN Ambon, 2020)
Education is the most important factor in order to increase the people's intelligence which is in accordance to the value of Pancasila, the basis of the Indonesian state, since character is the most important aspect in the nation's social life. Unfortunately, some parts (provinces) of Indonesia - especially Merauke for the example - doesn't receive quite education for the character-building and enrichment to happen. This is fatal enough considering good character equals good standards of living. This research aims to persuade all layers of society and the local government in order to initiate a great character-building education in Merauke, meanwhile it is also testing how much the government's intelligent character policy has been applied in Merauke. This research uses a qualitative and descriptive approach, along with the constructivist's paradigm. The results of the research have been concluded that the Merauke is still experiencing a crisis character in terms of education. It's about time that the local government, all layers of society, and all of those who are involved to assist one another to resolve the issue of character-building education - especially in Merauke. The conclusion of the research is that a strategic communication and social interactions in the form of awareness-raising can be the bridge for implementing a great character-building policy in Merauke. Keywords: education, character, standard of living, Merauke